Analisis Social Anxiety Narapidana Remaja dan Urgensinya dalam Layanan Bimbingan Konseling - Pratama, Farhan Fajar (At-Taujih: Jurnal Bimbingan dan Konseling Islam, 2025)
This study sought to investigate the level of social anxiety among juvenile inmates housed in the Tanjung Pati Class II Juvenile Justice and Rehabilitation Institution. A total of 19 participants were included in the study, utilizing a total sampling technique. Social anxiety was assessed via a self-report questionnaire employing the Likert scale method. Data analysis was conducted utilizing descriptive quantitative methods. Findings revealed that 63% of participants exhibited a high level of social anxiety, indicating a considerable prevalence of this psychological phenomenon within the juvenile inmate population. The type of offense committed and the duration of incarceration emerged as potential contributing factors to social anxiety among this specific population.